UPDATES FOR THE DEVELOPMENT OF 3D BIOPRINTING FROM DECELLULARIZED SCAFFOLDS: A NARRATIVE REVIEW - Costa Araújo, Marcelo; Arantes da Cunha, Maria Eduarda; Miguel, Camila Botelho; Maciel, Giovana Figueiredo; Trindade da Silva, Carlos Antônio; Freire Oliveira, Carlo José; Soares, Siomar de Castro; Rodrigues, Wellington (Acta Biologica Brasiliensia, 2025)
Regenerative medicine has significantly advanced in the past two decades, with tissue engineering playing a key role in expanding application possibilities and solutions for medical challenges. Decellularization of tissues and organs has accelerated bioengineering efforts, enhancing repair strategies for various injuries. This technique’s adaptability has led to its application across multiple tissue types, with certain methods demonstrating greater efficiency and potential for clinical integration. This study aims to document adjustments in decellularization techniques, key advances, and applications within tissue and organ repair. Using a retrospective and descriptive approach, this narrative review addresses both general and specific aspects of decellularization. Key topics include the underlying principles, primary techniques, advancements, applications, and future perspectives of decellularization methods. We expect this review to solidify the main evidence supporting tissue and organ repair strategies via decellularization and to provide insights or generate questions for further research, contributing to the enhancement of quality of life through more targeted primary studies.